2016
DOI: 10.1016/j.jconrel.2016.03.027
|View full text |Cite
|
Sign up to set email alerts
|

DAFODIL: A novel liposome-encapsulated synergistic combination of doxorubicin and 5FU for low dose chemotherapy

Abstract: PEGylated liposomes have transformed chemotherapeutic use of doxorubicin by reducing its cardiotoxicity; however, it remains unclear whether liposomal doxorubicin is therapeutically superior to free doxorubicin. Here, we demonstrate a novel PEGylated liposome system, named DAFODIL (Doxorubicin And 5-Flurouracil Optimally Delivered In a Liposome) that inarguably offers superior therapeutic efficacies compared to free drug administrations. Delivery of synergistic ratios of this drug pair led to greater than 90% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
42
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 76 publications
0
42
0
Order By: Relevance
“…This nanosystem offered superior therapeutic efficacies compared with free drug administrations and less cytotoxicity. The synergistic effect led to a high reduction (90%) in the tumour growth of murine 4T1 mammary carcinoma in vivo [135]. Example of immunotherapy combined with PDT was reported by Mir et al [136].…”
Section: Application Of Liposome As Multiactive Systemsmentioning
confidence: 82%
“…This nanosystem offered superior therapeutic efficacies compared with free drug administrations and less cytotoxicity. The synergistic effect led to a high reduction (90%) in the tumour growth of murine 4T1 mammary carcinoma in vivo [135]. Example of immunotherapy combined with PDT was reported by Mir et al [136].…”
Section: Application Of Liposome As Multiactive Systemsmentioning
confidence: 82%
“…Perhaps it is time to cast a fresh look at the present drug delivery approaches and re-engineer them to allow facile dual-targeting of both cell types simultaneously. A recent study by Mitragotri's group at University of California, Berkeley (CA, USA) showed an enhanced synergistic combinatorial therapy for tumor targeting by co-packaging two anticancer drugs in the same liposome carrier [15]. Such incorporation and synergistic use of more than one drug to enhance the efficacy of standard therapies is indeed the latest trend in targeted deliveries.…”
Section: Dual Targeting: a New Outlookmentioning
confidence: 99%
“…[7][8][9][10][11] As compared to the pure drug, PDCs show improved solubility and therapeutic efficacy, as well as reduced side effects and multi-drug resistance. [12][13][14] While conjugation to a polymer carrier was expected to prevent drug aggregation owing to slow and controlled drug release from the polymer backbone, it has been found that the polymer carrier does promote assembly of drugs, prior to or upon release, and play a role in tuning the architecture of drug nanoaggregates. We have experienced this effect while working on dextran-etoposide conjugates.…”
Section: Introductionmentioning
confidence: 99%